Epidemiology of Enterotoxigenic Escherichia coli infection in Minnesota, 2016–2017. (2020) - Buuck, S.; Smith, K.; Fowler, R. C.; Cebelinski, E.; Lappi, V.; Boxrud, D.; Medus, C.
Abstract: Enterotoxigenic Escherichia coli (ETEC) is a well-established cause of traveller's diarrhoea and occasional domestic foodborne illness outbreaks in the USA. Although ETEC are not detected by conventional stool culture methods used in clinical laboratories, syndromic culture-independent diagnostic tests (CIDTs) capable of detecting ETEC have become increasingly prevalent in the last decade. This study describes the epidemiology of ETEC infections reported to the Minnesota Department of Health (MDH) during 2016–2017. ETEC-positive stool specimens were submitted to MDH to confirm the presence of ETEC DNA by polymerase chain reaction (PCR). Cases were interviewed to ascertain illness and exposures. Contemporaneous Salmonella cases were used as a comparison group in a case-case comparison analysis of risk factors. Of 222 ETEC-positive specimens received by MDH, 108 (49%) were concordant by PCR. ETEC was the sixth most frequently reported bacterial enteric pathogen among a subset of CIDT-positive specimens. Sixty-nine (64%) laboratory-confirmed cases had an additional pathogen codetected with ETEC, including enteroaggregative E. coli ( n = 40) and enteropathogenic E. coli ( n = 39). Although travel is a risk factor for ETEC infection, only 43% of cases travelled internationally, providing evidence for ETEC as an underestimated source of domestically acquired enteric illness in the USA.